On partial defaults in portfolio credit risk: Comparing economic and regulatory view - Rafael Weißbach; Carsten von Lieres und Wilkau (Universität Dortmund, Sonderforschungsbereich 475 - Komplexitätsreduktion in Multivariaten Datenstrukturen, 2006)
Most credit portfolio models calculate the loss distribution of a portfolio consisting solely of performing counterparts. We develop two models that account for defaulted counterparts in the calculation of the economic capital. First, we model the portfolio of non-performing counterparts standalone. The second approach derives the integrated loss distribution for the non-performing and the performing portfolio. Both calculations are supplemented by formulae for contributions of the single counterpart to the economic capital. Calibrating the models allows for an impact study and a comparison with Basel II.
Keywords: 519